Muamalat Bank Mosque Management Training ‘’The Best Social Marketing’’ Viewed From Public Relations Theories - Anggaraksa Adwitiya Arrazy; Juan Malik Frederick Turpyn (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
The development of Information and Communication Technology makes it easier for humans to carry out their daily activities. Every element of society can certainly move to create a better human life. One of them is Bank Muamalat. This company helps mosques in Java and Sumatra in carrying out mosque management activities. This study also aims to analyze and examine descriptively the management of the Muamalat Bank mosque which was awarded as